PERBANDINGAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN MODEL PROBLEM-BASED LEARNING DAN NUMBERED HEADS TOGETHER BERBASIS STUDENT CREATED CASE STUDIES - Dwi Ayu Lestari; Joko Ariyanto; Harlita Harlita (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
COMPARISON OF STUDENTS' CRITICAL THINKING SKILLS WITH PROBLEM-BASED LEARNING AND NUMBERED HEADS TOGETHER BASED ON STUDENT-CREATED CASE STUDIES MODELSAbstractThe study's purpose was to determine the differences in students' critical thinking skills between the problem-based learning and numbered heads together based on student-created case studies model on biology subjects in class X of SMA 2 Karanganyar in the academic year 2018/2019. This research is a quasi-experiment, and the research design used a posttest only with non-equivalent groups. The sampling technique is cluster sampling. Samples were 72 students, namely X IPA 3 as an experimental class 1 and X IPA 1 as an experimental class 2. Data collection techniques were using essay tests, observation sheets, and documentation. The data analysis used was an independent t-test. The calculation of the difference in the average posttest of the two groups for critical thinking skills showed a calculated value of 2,243 and the table value of 1.994 with a significance (α = 0,05). The calculation results show that tcount > ttable, which means there is a significant difference in the students' critical thinking skills in the class between the problem-based learning model and numbered heads together based on the student-created case studies model. AbstrakTujuan penelitian untuk mengetahui perbedaan keterampilan berpikir kritis siswa antara model pembelajaran problem based learning dengan numbered heads together berbasis student created case studies pada mata pelajaran biologi kelas X SMA Negeri 2 Karanganyar tahun pelajaran 2018/2019. Penelitian ini merupakan penelitian eksperimen semu (quasy experiment). Desain penelitian yang digunakan adalah posttest only with non-equivalent group. Teknik pengambilan sampel dengan cluster sampling. Sampel yang diambil berjumlah 72 siswa yaitu X IPA 3 sebagai kelas eksperimen 1 dan X IPA 1 sebagai kelas eksperimen 2. Teknik pengumpulan data menggunakan tes essay, lembar observasi, dan dokumentasi. Analisis data yang digunakan yaitu uji independent t-test. Hasil perhitungan perbedaan rata-rata posttest kedua kelompok untuk keterampilan berpikir kritis menunjukkan nilai hitung sebesar 2,243 dan nilai ttabel sebesar 1.994 dengan signifikansi (α=0,05). Hasil perhitungan menunjukkan bahwa thitung > ttabel, sehingga terdapat perbedaan signifikan keterampilan berpikir kritis siswa yang diajarkan menggunakan model problem based learning dengan numbered heads together berbasis student created case studies.